(untitled) (Medicine Anthropology Theory, 2023)
This Special Section explores questions of method and positionality attached to moral agency in mental healthcare, which give rise to novel methodological and theoretical approaches to everyday life in the clinical and non-clinical spaces where such ‘care’ occurs. Moral agency is the ability to be perceived as a ‘good enough’ person, which makes possible intimate relationships with others that are needed to thrive in many social contexts (Myers 2015). In this introduction, we draw on Mattingly’s (2014) notion of everyday moral laboratories: an exploratory attention to moral life as innovative method, episteme, and interpersonal collaboration. Exploring the everyday moral laboratories where people struggle to replenish or protect their moral agency and so create meaning and relationships in their lives is a key focus of this Special Section. For interdisciplinary ethnographers working in spaces intended for care, such experimentation yields opportunities to more creatively and proactively inform that care—the everyday, the ordinary, and the extraordinary—that centres on helping our interlocutors replenish moral agency and thrive.